The feeding ecology of the black rhinoceros (Diceros bicornis minor) in Hluhluwe-Umfolozi Park, with special reference to the probable causes of the Hluhluwe population crash - Emslie, Richard (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.) -- University of Stellenbosch, 1999.